To solve the equation \( x^2 - 5x - 3 = 0 \) using the Quadratic Formula, we can use the formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
For the equation \( ax^2 + bx + c = 0 \), we have:
- \( a = 1 \)
- \( b = -5 \)
- \( c = -3 \)
Now, we can calculate \( b^2 - 4ac \):
\[ b^2 - 4ac = (-5)^2 - 4(1)(-3) = 25 + 12 = 37 \]
Since \( b^2 - 4ac \) is positive, we will have two real solutions. Now, substituting the values into the Quadratic Formula:
\[ x = \frac{-(-5) \pm \sqrt{37}}{2(1)} = \frac{5 \pm \sqrt{37}}{2} \]
Thus, the two solutions are:
\[ x = \frac{5 + \sqrt{37}}{2} \quad \text{and} \quad x = \frac{5 - \sqrt{37}}{2} \]
The final answer is:
-
\( x = \frac{5 + \sqrt{37}}{2}, \frac{5 - \sqrt{37}}{2} \)
-
There are no real solutions (this option is incorrect as we found real solutions).